Carbohydrate metabolism before and after dehiscence in the recalcitrant pollen of pumpkin (Cucurbita pepo L.). (1st December 2014) - Carrizo García, C.; Guarnieri, M.; Pacini, E.; Arroyo, J.
Abstract Pumpkin (Cucurbita pepo L.) pollen is starchy, sucrose‐poor and recalcitrant, features opposite to those of several model species; therefore, some differences in carbohydrate metabolism could be expected in this species. By studying pumpkin recalcitrant pollen, the objective was to provide new biochemical evidence to improve understanding of how carbohydrate metabolism might be involved in pollen functioning in advanced stages. Four stages were analysed: immature pollen from 1 day before anthesis, mature pollen, mature pollen exposed to the environment for 7 h, and pollen rehydrated in a culture medium. Pollen viability, water and carbohydrate content and activity of enzymes involved in carbohydrate metabolism were quantified in each stage. Pollen viability and water content dropped quickly after dehiscence, as expected. The slight changes in carbohydrate concentration and enzyme activity during pollen maturation contrast with major changes recorded with ageing and rehydration. Pumpkin pollen seems highly active and closely related to its surrounding environment in all the stages analysed; the latter is particularly evident among insoluble sucrolytic enzymes, mainly wall‐bound acid invertase, which would be the most relevant for sucrose cleavage. Each stage was characterised by a particular metabolic/enzymatic profile; some particular features, such as the minor changes during maturation, fast sucrolysis upon rehydration or sharp decrease in insoluble sucrolytic activity with ageing seem to be related to the lack of dormancy and recalcitrant nature of pumpkin pollen.